INTEGRASI BUDAYA LOKAL DAN LINGKUNGAN DALAM KEGIATAN PASRAMAN KILAT DAN EDUKASI SAMPAH DI SD NEGERI 4 PEGUYANGAN, DENPASAR - Anak Agung Komang Suardana; Ni Wayan Nia Cahyani; Ni Ketut Rusmiyanti Cahyani; I Made Kerta Jaya; Ida Ayu Made Dwi Cempaka; I Putu Julio Andhika Putra (UNHI Press, 2026)
The increasingly alarming waste management crisis in Indonesia, particularly in Bali, requires an educational approach based on community and local wisdom. This article describes the implementation of the Thematic Community Service Program (KKN) by Group 12 students from the Indonesian Hindu University (UNHI) at Peguyangan 4 Elementary School, which integrates environmental education with local cultural values ​​through the